Scarica il testo completo in PDF Quando la religione si interseca con la tutela di genere: quale impatto sulle dinamiche dell’accoglienza? (prime osservazioni a margine di Cass., sez. I, 24 novembre 2017, n. 28152) (Stato, Chiese e pluralismo confessionale, 2018)
SOMMARIO: 1. Fenomeno migratorio, istanze di protezione internazionale e risposte degli ordinamenti europei - 2. Riconoscimento dello status di rifugiato e fattore religioso - 3. La recente pronunzia n. 28152 del 2017 della Corte di Cassazione - 4. La valorizzazione della prospettiva di genere nel sistema di protezione internazionale - 5. L’intersezione religione/genere quale pivot di una protezione rafforzata di soggetti particolarmente deboli.The Intersection between Religion and Gender Protection: Which Impact on the Dynamics of Hospitality? (Preliminary Remarks to Court of Cassation, Section I, 24 November 2017, No. 28152)ABSTRACT: The intersection between immigration, citizenship, integration in the EU countries is a challenging topic for scholars and religion is becoming a crucial factor. Transnational space allows the development of new meanings, negotiation of identities, interaction of religious actors and practices and integration/participation has an impact on the identity of migrants. The increase of migrations from non-European countries, and the impact of new religious needs underlines the question of whether religious belonging is a factor of either empowerment or disempowerment in the host society. At the same time, migrations in an era of economic crisis emphasize skepticism and hostility towards Islamic groups; refugees and asylum seekers, and the questions connected with international protection have become other controversial issues, contributing to the development of a growing anti-immigrant attitude. Modern democracies are expected to offer answers to increasing demands of international protection; at the same time international protection is becoming a strategic tool to obtain hospitality in European countries, and to avoid the limits connected  to access for economic reasons. Recent Italian case law witnesses the development of a gender-sensitive perspective and focuses on the increasing link between religion, gender and international protection.